Synthesis of acidic vinylcyclopropanes for dental applications. Issue 10 (21st June 2017) - Catel, Yohann; Fässler, Pascal; Fischer, Urs; Pesch, Carmen; Pruvost, Chloé; Tauscher, Sven; Moszner, Norbert
Abstract: The multistep synthesis of four new acidic vinylcyclopropanes is described. These monomers were fully characterized using 1 H NMR, 13 C NMR and 31 P NMR spectroscopy and high‐resolution mass spectrometry. The homopolymerization of the corresponding polymerizable di‐ tert ‐butyl phosphates as well as the copolymerization of each acidic monomer with 1, 1‐diethoxycarbonyl‐2‐vinylcyclopropane were investigated using photo‐differential scanning calorimetry with bis(4‐methoxybenzoyl)diethylgermane as photoinitiator. Self‐etch adhesives based on the synthesized acidic vinylcyclopropanes are able to achieve a strong bond between a dental composite and both dentin and enamel. Flowable composites containing these acidic vinylcyclopropanes exhibit good mechanical properties. The replacement of methacrylates by vinylcyclopropanes leads to a significant reduction of the shrinkage stress of flowable composites. © 2017 Society of Chemical Industry Abstract : The synthesis of four new acidic vinylcyclopropanes is described. Their photopolymerization behaviour was investigated. The performance of self‐etch adhesives and low‐shrinkage flowable composites based on these monomers was evaluated.